Discordances in Estrogen Receptor Status, Progesterone Receptor Status, and HER2 Status Between Primary Breast Cancer and Metastasis. (30th May 2013) - Curtit, Elsa; Nerich, Virginie; Mansi, Laura; Chaigneau, Loic; Cals, Laurent; Villanueva, Cristian; Bazan, Fernando; Montcuquet, Philippe; Meneveau, Nathalie; Perrin, Sophie; Algros, Marie‐Paule; Pivot, Xavier
Abstract : Background: The primary aim of this retrospective study was to investigate intraindividual correlation of estrogen receptor (ER) status, progesterone receptor (PR) status, and HER2 status between primary breast cancer and metastatic breast cancer (mBC). Secondary aims included patients' characteristics, overall survival, feasibility of histopathological evaluation in the metastatic setting, and predictive factors associated with receptors status discordance. Methods: Patients with either biopsy of metastatic relapse or surgery of metastasis were identified. Demographics, tumor characteristics, treatment characteristics, and ER, PR, and HER2 statuses were retrospectively obtained in patients' reports. Receptors statuses were assessed by immunohistochemistry with a positivity cutoff of more than 10% for ER and PR. HER2 was considered as positive if overexpression was scored at 3+ in immunohistochemistry or if amplification ratio was >2 in fluorescent in situ hybridization. Results: From a cohort of 489 patients with mBC, 269 patients had histopathological samples of metastatic relapse. Histopathological analysis of the specimen confirmed the diagnosis of mBC in 235 patients. Discordance in one or more receptors between primary breast cancer and mBC was found in 99 patients (42%). A switch in receptor status was identified for ER in 17% of tumors ( p = 4 × 10 −3 ), PR in 29% of cancers ( p < 4 × 10 −4 ), and HER2 in 4% of lesions ( p = .16). Exposure to chemotherapy and to anthracycline‐based chemotherapy was statistically associated with switches in ER status. Seven (2%) second malignancies and three benign diseases (1%) were diagnosed. Conclusions: This study confirms that discordance in ER and PR receptor expression between the primary breast tumor and the corresponding metastatic lesions is high, whereas HER2 status remains relatively constant. Chemotherapy, and specifically anthracycline‐based chemotherapy, was associated with switch in ER status. These results were obtained in a selected population of patients; further studies are warranted to confirm these data and to determine the interest of systematic rebiopsy in the metastatic setting. Abstract : This retrospective study confirms that discordance in estrogen receptor (ER) and progesterone receptor expression between the primary breast tumor and the corresponding metastatic lesions is high, whereas HER2 status remains relatively constant. Chemotherapy, and specifically anthracycline‐based chemotherapy, was associated with switch in ER status. Abstract : 摘要 背景 ：该回顾性研究的主要目的是研究个体内原发乳腺癌和转移乳腺癌（mBC）雌激素受体（ER）状态、孕激素受体（PR）状态和HER2状态的相互关系。次要目的包括患者特征、总生存、转移灶组织病理学评价的可行性以及与受体状态不一致性相关的预测因子。 方法 ：确定有复发转移灶活检或转移灶手术的患者。从患者报告中回顾性获取人口统计学资料、肿瘤特征、治疗特征和 ER、PR以及 HER2 状态。通过免疫组化评估受体状态。ER 和 PR 的阳性界值为> 10%。HER2 免疫组化评分 3+ 或荧光原位杂交扩增比值 >2 考虑为 HER2 阳性。 结果 ：489 例 mBC 患者队列中的 269 名患者有转移性复发组织病理样本。235 例患者标本经组织病理学分析确认诊断为 mBC。在 99 名患者中（42%）发现原发乳腺癌和 mBC 之间有 1 种或更多受体不一致。17% 的肿瘤确认有 ER的转变（ p = 4×10 ‐3 ）, 29%有 PR 转变（ p < 4×10 ‐4 ），4% 有 HER2 转变（ p = 0.16）。暴露于化疗和蒽环类为基础化疗与 ER 状态转变在统计学上相关。7 例患者（2%）诊断为第二原发恶性肿瘤，3 例患者（1%）诊断为良性病变。 结论 ：本研究确定了在原发乳腺肿瘤和相应的转移灶中 ER 和 PR 受体表达的不一致性较高，而 HER2 状态保持相对稳定。化疗，特别是蒽环类为基础的化疗，和 ER 状态转变相关。这些结果是在经过选择的患者人群中获得的；需要开展进一步研究以确认这些数据并确定在转移阶段进行系统重复活检的益处。 The Oncologist 2013;18:667‐674